2018
DOI: 10.1038/s41598-018-34553-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic agent, sodium oxybate, improves dystonic symptoms via reduced network-wide activity

Abstract: Oral medications for the treatment of dystonia are not established. Currently, symptoms of focal dystonia are managed with botulinum toxin injections into the affected muscles. However, the injection effects are short-lived and not beneficial for all patients. We recently reported significant clinical improvement of symptoms with novel investigational oral drug, sodium oxybate, in patients with the alcohol-responsive form of laryngeal focal dystonia. Understanding the mechanism of action of this promising oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Investigations in patients with SD and SCGE-MD support a pivotal role of the cerebellum and Purkinje cells in these disorders. In an fMRI study of SD patients treated with a single dose of Xyrem, clinical improvement in dysphonia and reduction in vocal breaks correlated with normalization of cerebellar activation [72]. In a PET study, symptomatic SCGE-MD patients demonstrated activation of cerebellar cortex and dentate compared to non-manifesting SCGE carriers and healthy controls [70].…”
Section: B: Evidence Of the Role Of The Cerebellum In Alcoholresponsimentioning
confidence: 89%
See 1 more Smart Citation
“…Investigations in patients with SD and SCGE-MD support a pivotal role of the cerebellum and Purkinje cells in these disorders. In an fMRI study of SD patients treated with a single dose of Xyrem, clinical improvement in dysphonia and reduction in vocal breaks correlated with normalization of cerebellar activation [72]. In a PET study, symptomatic SCGE-MD patients demonstrated activation of cerebellar cortex and dentate compared to non-manifesting SCGE carriers and healthy controls [70].…”
Section: B: Evidence Of the Role Of The Cerebellum In Alcoholresponsimentioning
confidence: 89%
“…One hour after administration of two gm of Xyrem, myoclonus was improved. The final two patients, #s 12 and 13, participated in a study of the effects of Xyrem on SD with functional MRI [72].…”
Section: Video: Alcohol-responsive Movement Disorders-a Unifying Hypomentioning
confidence: 99%
“…As a matter of fact, it has been previously suggested that idiopathic focal dystonias may be considered as a purely functional disorder (10, 11, 24, 58, 59). Network-wide differences in brain activation that disappear with successful symptomatic treatment have been observed in functional MRI (6062).…”
Section: Discussionmentioning
confidence: 99%
“…When ingested orally, it could be quickly absorbed and cross the blood–brain barrier, converted into GHB within the brain ( 97 ). It is proved to be an agonist of most GABA B receptors as well ( 98 ), which also suggests that it might deliver a similar effect to ethanol.…”
Section: Progress On Pharmacotherapy For Ermdsmentioning
confidence: 99%
“…When ingested orally, it could be quickly absorbed and cross the bloodbrain barrier, converted into GHB within the brain (97). It is proved to be an agonist of most GABA B receptors as well (98), which also suggests that it might deliver a similar effect to ethanol. Recent clinical trials showed that over half of patients with ethanol-responsive movement disorders achieved symptom improvement after administration of sodium oxybate, and the improvement of myoclonus at rest usually occurs earlier than that of myoclonus in action.…”
Section: Sodium Oxybatementioning
confidence: 99%